Existential Medicine Essays on Health and Illness - Aho, Kevin (Rowman & Littlefield International, 2018)
Existential Medicine explores the recent impact that the philosophies of existentialism, phenomenology, and hermeneutics have had on the health care professions. A growing body of scholarship drawing primarily on the work of Martin Heidegger and other influential twentieth-century figures such as Maurice Merleau-Ponty, Jean-Paul Sartre, and Hans-Georg Gadamer has shaped contemporary research in the fields of bioethics, narrative medicine, gerontology, enhancement medicine, psychiatry and psychotherapy, and palliative care, among others. By regarding the human body as a decontextualized object, the prevailing paradigm of medical science often overlooks the body as it is lived. As a result, it fails to critically engage the experience of illness and the core questions of 'what it means' and 'what it feels like' to be ill. With work from emerging and renowned scholars in the field, this collection aims to shed light on these issues and the crucial need for clinicians to situate the experience of illness within the context of a patient's life-world. To this end, Existential Medicine offers a valuable resource for philosophers and medical humanists as well as health care practitioners.